Understanding GPs' clinical reasoning processes involved in managing patients suffering from multimorbidity: A systematic review of qualitative and quantitative research. Issue 9 (5th May 2021) - Cairo Notari, Sarah; Sader, Julia; Caire Fon, Nathalie; Sommer, Johanna Maria; Pereira Miozzari, Anne Catherine; Janjic, Danilo; Nendaz, Mathieu; Audétat, Marie‐Claude
Abstract: Background: Most consultations in primary care involve patients suffering from multimorbidity. Nevertheless, few studies exist on the clinical reasoning processes of general practitioners (GPs) during the follow‐up of these patients. The aim of this systematic review is to summarise published evidence on how GPs reason and make decisions when managing patients with multimorbidity in the long term. Methods: A search of the relevant literature from Medline, Embase, PsycINFO, and ERIC databases was conducted in June 2019. The search terms were selected from five domains: primary care, clinical reasoning, chronic disease, multimorbidity, and issues of multimorbidity. Qualitative, quantitative, and mixed‐methods studies published in English and French were included. Quality assessment was performed using the Mixed Methods Appraisal Tool. Results: A total of 2 165 abstracts and 362 full‐text articles were assessed. Thirty‐two studies met the inclusion criteria. Results showcased that GPs' clinical reasoning during the long‐term management of multimorbidity is about setting intermediate goals of care in an ongoing process that adapts to the patients' constant evolution and contributes to preserve their quality of life. In the absence of guidelines adapted to multimorbidity, there is no single correct plan, but competing priorities and unavoidable uncertainties. Thus, GPs have to consider and weigh multiple factors simultaneously. In the context of multimorbidity, GPs describe their reasoning as essentially intuitive and seem to perceive it as less accurate. These clinical reasoning processes are nevertheless more analytical as they might think and rooted in deep knowledge of the individual patient. Conclusions: Although the challenges GPs are facing in the long‐term follow‐up of patients suffering from multimorbidity are increasingly known, the literature currently offers limited information about GPs' clinical reasoning processes at play. GPs tend to underestimate the complexity and richness of their clinical reasoning, which may negatively impact their practice and their teaching.